Faktory ovplyvnujúce vulnerabilitu l'avej predsiene pri rýchlej transezofageálnej stimulácii predsiení - Stancák, B; Misíková, S; Schroner, Z; Pella, J (Vnitrni lekarstvi, 1994)
Atrial fibrillation (AF) is associated with a higher morbidity and mortality because of the risk of systemic or pulmonary embolism as well as the negative impact on cardiac function. The authors investigate in the submitted paper factors influencing the vulnerability of atria during transoesophageal atrial stimulation (TESP). The group comprised 68 patients with a sinus rhythm, mean age 56.9 +/- 17.9 years. Depending on the response to rapid atrial stimulation, the patients were divided into three groups. In group I (small disposition to AF) they revealed a significantly lower age, the relative thickness of the left ventricular wall assessed by echocardiography and the dimension of the left atrium, as compared with groups with a medium increased (II) and high disposition (III) for AF. In group III hypertonic changes on the fundus were found more frequently, as well as anamnestic data on hypertension, diabetes and pathological values of the recovery period of the sinoatrial node. At the same time significantly lower values of the rate of the E wave were observed and of the ratio of amplitudes and E/A integrals from the Doppler record of the mitral valve. The weight of the left ventricle and its index by groups increased, however the changes did not attain statistical significance. Indicators of left ventricular systolic function did not differ. The authors conclude that the main independent factors which determine the response to provoked AF by the TESP method are the diastolic left ventricular function documented by the Doppler method, the diameter of the left atrium, the automation of the SA node. Less important factors are left ventricular hypertrophy and age.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: dospělí; senioři nad 80 let; Humans; Heart Atria; lidé středního věku; Middle Aged; Aged, 80 and over; fibrilace síní; Cardiac Pacing, Artificial; Risk Factors; mužské pohlaví; Adult; Adolescent; rizikové faktory; kardiostimulace umělá; dopplerovská echokardiografie; srdeční síně; ženské pohlaví; Echocardiography, Doppler; lidé; mladiství; Atrial Fibrillation; Aged; senioři; Male; Female